Reparto de tráfico basado en métricas de rendimiento en escenarios con multiconectividad - Burgueño Romero, Jesús; De la Bandera Cascales, Isabel; Palacios, David; Barco-Moreno, Raquel (My University, 2019)
Multi-connectivity (MC) is one of the most relevant features to be introduced in 5G networks, allowing users to simultaneously aggregate radio resources from several network nodes to improve both reliability and data rates. Until now, no policies have been defined to determine the amount of traffic to be held by each of the Component Carriers (CCs) provided by the different serving nodes. This paper shows how a traffic split, which is dependent of user and network performance metrics, allows the benefits of MC to be further enhanced in terms of throughput when compared to a homogeneous traffic split among the CCs provided by several serving nodes. To that end, several simulations have been carried out with different user distributions.
Keywords: Redes de información; Sistemas de comunicaciones inhalámbricos; Telecomunicaciones